Treading on sacred grounds : places of worship, local planning and religious freedom in Australia - Villaroman, Noel G. (Studies in religion, secular beliefs, and human rights., 2015)
In Treading on Sacred Grounds: Places of Worship, Local Planning and Religious Freedom in Australia, Noel Villaroman analyses the spatial or structural constraints to religious freedom as a result of local planning regulations in Australia.